Indomethacin Increases the Efficacy of Oxygen Utilization of Colonic Mitochondria and Uncouples Hepatic Mitochondria in Tissue Homogenates From Healthy Rats - Herminghaus, Anna; Buitenhuis, Albert J.; Schulz, Jan; Truse, Richard; Vollmer, Christian; Relja, Borna; Bauer, Inge; Picker, Olaf (Frontiers in Medicine, 2020)
Background: Studies suggest that indomethacin (Indo) exhibits detrimental changes in the small intestine (microvascular disorder, villus shortening and epithelial disruption), mainly due to mitochondrial uncoupling. The effects of Indo on colon and liver tissue are unclear. The aim of this study was to determine the effects of Indo on mitochondrial respiration in colonic and hepatic tissue. Methods: Mitochondrial oxygen consumption was assessed in colon and liver homogenates from healthy rats. Homogenates were incubated without drug (control) or Indo (colon: 0.36, 1, 30, 179, 300, 1000, 3000 µM; liver: 0.36, 1, 3, 10, 30, 100, 179 µM; n=6). State 2 (substrate-dependent) and state 3 (ADP-dependent respiration) were evaluated with respirometry. The respiratory control index (RCI) was derived and the ADP/O ratio was calculated. Statistics: Data presented as % of control, min/median/max, Kruskal-Wallis+Dunn’s correction, *p<0.05 vs. control. Results: Indo had no effect on RCI of colonic mitochondria. ADP/O ratio increased in complex I at concentrations of 1000 and 3000 µM (Indo 1000 µM: 113/158.9/166.9 %*; Indo 3000 µM: 151.5/183/361.5 %*) and in complex II at concentrations of 179 and 3000 µM vs. control (179 µM: 111.3/142.2/156.7 %*; 3000 µM: 132:4/175/339.4 %*). In hepatic mitochondria RCI decreased at 179 µM for both complexes vs. control (complex I: 25.6/40.7/62.9 %*, complex II: 57/73.1/74.9 %*). The ADP/O ratio was only altered in complex I at a concentration of 179 µM Indo vs. control (Indo 179 µM: 589.9/993.7/1195 %*). Conclusion: Indo affected parameters of mitochondrial function in an organ-specific and concentration-dependent manner. In colonic tissue, RCI remained unaltered whereas the ADP/O ratio increased. Indo at the highest concentration decreased the RCI for both complexes in hepatic mitochondria. The large increase in ADP/O ratio in complex I at the highest concentration likely reflects terminal uncoupling.